Study on Day Care Transfusion Services in Transfusion Medicine Department of a Tertiary Care Hospital (Bangladesh Medical Journal, 2019)
Transfusion of blood components and derivatives in day care unit is an eminent part of management of transfusion dependent patients. Day care transfusion service is an alternative to hospital admission and beneficial for those patients who receive blood more frequently for their survival. The aim of present study is to assess Transfusion Services provided in a Day Care Unit (DCU) of a tertiary care hospital. This study was carried out in DCU of Transfusion Medicine Department, Bangabandhu Sheikh Mujib Medical University, (BSMMU), in Dhaka during January to December 2014. Data were collected from record registers. Recorded retrospective data were analyzed as percentage and proportion. Total recipients were 718. Among those 424 (59.05%) were male and 294 (40.95%) were female and 562 (78.27%) were between 10 to 40 years. A total of 8587 units of blood components were used during this period. Red Cell Concentrate was most commonly utilized product 6388 (74.39%)  followed by FFP 1360 (15.83%), Platelet Concentrate 544 (6.33%), Whole blood 260 (3.05%) and Cryoprecipitate 35(0.40%). Transfusion was required more frequently in thalassaemic 365(50.88%) patients. Haemophilia 77(10.72%) and aplastic anaemia patients 49 (6.82%) were next high. The main transfusion reaction observed during transfusion was febrile non-haemolytic reactions. For increasing use of specific blood product and hassle free transfusion services this kind of day care unit services should be strengthened. Long term study of this kind will help us to develop safe clinical transfusion practice.Bangladesh Med J. 2019 May; 48 (2): 28-31